2021
DOI: 10.3390/s21062193
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive-Emotional Design and Study of Architectural Space: A Scoping Review of Neuroarchitecture and Its Precursor Approaches

Abstract: Humans respond cognitively and emotionally to the built environment. The modern possibility of recording the neural activity of subjects during exposure to environmental situations, using neuroscientific techniques and virtual reality, provides a promising framework for future design and studies of the built environment. The discipline derived is termed “neuroarchitecture”. Given neuroarchitecture’s transdisciplinary nature, it progresses needs to be reviewed in a contextualised way, together with its precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 472 publications
(411 reference statements)
0
50
0
5
Order By: Relevance
“…A better understanding of the human–environment interaction could contribute to informing design strategies in ways to optimize psychological well-being and mental health [ 11 ]. Although the discussion has been initiated, a commonly accepted methodology across disciplines is still lacking [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the human–environment interaction could contribute to informing design strategies in ways to optimize psychological well-being and mental health [ 11 ]. Although the discussion has been initiated, a commonly accepted methodology across disciplines is still lacking [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The common requirements about positive perception are as follows (numbers indicate the frequency of mention): learning atmosphere (5), positive psychological hint (4), silence (5). While, the negative spatial characteristics which have the possibility to interfere with learning and reduce the visiting desire are nervous atmosphere (5), uncomfortable sitting (3), absence of space division (2), fixed seat (2), narrow personal space (3), poor air quality (4), limited supply hubs (2), chaotic people flow (3), smell of food (1). Examples of sentences are shown below: A1 (male, second year undergraduate, engineering major, R-I-Vis-Seg): I feel the place has overly serious atmosphere which brings back memories of hard lessons.…”
Section: Perception and Preference Of Learning Spacesmentioning
confidence: 99%
“…For the past decade, much attention has been paid on the influence of building spaces on people's cognitive activities [1][2][3][4]. Some special spatial characteristics will stimulate the operations of the undirected attention and make it rest, which results in positive changes of mind and body, including mental restoration, stress recovery, efficient cognitive process, good emotions, and so on [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies participants reported higher beautiful judgements for 2D representations of architectures with high ceiling and open spaces 2,3 , which were also perceived as more pleasant 4 . The presence of windows is also typically linked to pleasant sensation 5 , since they enable an outdoor view and create a more spacious perception of the environment 6,7 . Moreover, cold colours receive typically higher valence ratings with respect to warm ones, thus moving people preferences towards cold environments [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%